Program dan Aktiviti Dakwah Nahdlatul Ulama (NU) Masakini - Mohd. Zin, Ab. Aziz (Jurnal Usuluddin, 1997)
The article discusses the activities of NU which is the biggest dawah organisation in Indonesia. The activities of NU covers almost all aspects of contemporary human life.